Acute multifocal hemorrhagic retinal vasculitis in a child: a case report. Issue 1 (December 2016) - Ghannam, Malik; Naseemuddin, Mohammed; Weiser, Peter; Mason, John
Abstract Background Acute Multifocal Hemorrhagic Retinal Vasculitis (AMHRV) is a rare disease with unknown incidence that presents with abrupt onset of visual loss associated with retinal vasculitis, retinal hemorrhage, non-confluent posterior retinal infiltrates, vitreous cellular inflammation and papillitis in, otherwise, healthy adult individuals. The reported treatment options for Acute Multifocal Hemorrhagic Retinal Vasculitis are oral corticosteroids, intravitreal ganciclovir and laser photocoagulation or vitrectomy. We report a child with Acute Multifocal Hemorrhagic Retinal Vasculitis who was treated with aggressive immunosuppressive therapy resulting in a favorable visual outcome. Case presentation A retrospective case report of a 10-year-old African American girl who developed unilateral Acute Multifocal Hemorrhagic Retinal Vasculitis, which later on progressed bilaterally. We conducted a review of the clinical, laboratory and photographic records to evaluate her functional and anatomic outcome after aggressive immunosuppressive treatment. During the first 4 months of treatment of OD with intravitreal ganciclovir, intravitreal dexamethasone and systemic prednisone, the change in vision in OD improved from light perception (LP) to counting fingers (CF). During the next 18 months of aggressive systemic treatment of OD and the newly affected left eye (OS), the change in vision improved from CF in OD and CF in OS to 20/200 in OD and 20/80 in OS. Management during the 18-month interval included rituximab infusions, cyclophosphamide/methylprednisolone infusions, prednisone and mycophenolate. Conclusions This is the first reported case of Acute Multifocal Hemorrhagic Retinal Vasculitis occurring in a child. Ophthalmologists should be aware of the need to treat severe Acute Multifocal Hemorrhagic Retinal Vasculitis with aggressive immunosuppressive agents in collaboration with rheumatologists to obtain the best possible visual outcome.